The Role of Teachers on the Sexual Violence Prevention to Early Adolescents - Zahra, Rana; Abiddin, Andi Hayyun; Mugianti, Sri (Health Access Journal, 2024)
Sexual violence in Indonesia has become a phenomenon that is rampant in society. Currently, the number of reported cases of victims of sexual violence in Indonesia recorded through the Online Information System for the Protection of Women and Children has reached 23,993 cases. Teachers have a very important role in teaching adolescents about sex education, so that they can avoid sexual deviance. The purpose of this study is to find out the role of teachers as educators in an effort to provide sexual violence prevention education to early adolescents. This study uses a quantitative descriptive research design with a population of 48 teachers selected using the total sampling technique. Data collection was carried out by questionnaire through google form and analyzed using the guttman scale. The conclusion of the test results carried out is valid and reliable. Data collection was carried out in January - February 2024 at MTsN 8 Blitar. The results showed that the most said parameter was the role of teachers as educators in an effort to provide sexual violence prevention education to early adolescents, namely explaining the maturity of attitudes to students, reaching 93.33percent. There are differences of opinion among teachers regarding sexual education, due to taboos and stigmas, lack of adequate training and skills in providing sexual education. With this, it is hoped that teachers will improve their skills and competencies by participating in existing training.